Os desafios da introdução de uma inovação tecnológica no agroextrativismo tradicional: análise do caso das roças orgânicas no Médio Mearim - Gusmão, Luiz Antônio (2009)
This study analyzes the process of technological innovation in the agroextractivism developed by smallholders of the community of Três Poços, city of Lago dos Rodrigues, Maranhão state, where the babassu palm (Attalea speciosa Mart.) dominates the landscape. The aim of our study was the replacement of the traditional agroextrativism in which besides collecting babassu nuts staple crops are planted in available areas after burning by a permanent and organic agroextrativism without the use of fire. The theoretical approach is based on technological innovation in agriculture and research related to the extraction of babassu nuts in the region. Results were obtained through interviews with local farmers involved in the project, observations of their management practices and data collection of the evolution of crop areas with traditional and organic agroextrativism, yield of staple food crops (rice, cowpea, maize and cassava) and babassu nut as well as labor force necessary in both systems. The results showed that the traditional agroextrativism achieved its limit with respect to the use of land available and is consequently unable to keep set aside areas for several years. However, the proposal of technological innovation with the organic agroextrativism does not guarantee food security for households besides increasing demand for labor, which ultimately undermine the abandonment of the traditional agroextrativism. In addition, there is an urgent need to tackle problems related to production, pests and weeds in the organic agroextrativism. In conclusion, despite the above mentionated limitations of the proposed organic agroextrativism and the fact that it still does not guarantee food security for smallholders, the unsustainability of the traditional agroextrativism is the only reason for continued development of the organic agroextrativism.